A review of CO₂ capture adsorbents: carbonate/oxide systems and aerogel synthesis - Lawrie, Clark (Kansas State University, 2023)
Carbon dioxide (CO₂) emissions have created a global crisis needing to be addressed. Extensive studies have been conducted on reducing these emissions using adsorbent materials with technologies that capture, store, and utilize the CO₂. Elements that exist in nature such as alkali and alkaline earth metals are observed to have favorable properties that lead to high sorption capacities when paired with carbonate and oxide systems. These sorbents have their shortcomings, especially when being regenerated for reuse, which require considerations with improved characteristics. With the capability of having low regeneration temperatures as well as above average CO₂ adsorption capacity, aerogels need to be a strong contender in remedying climate change and global warming through CO₂ capture. This review discusses recent work completed for carbonate and oxide systems, the aerogel synthesis method, and the nanocomposites made with them combined having desirable attributes in capturing CO₂.
Keywords: Aerogel; Metal oxides; Carbonate; Adsorbents; CO₂ capture